Premature Coronary Artery Disease in Young Male Patient with Strong Family History - Dea Arie Kurniawan; Mohammad Saifur Rohman; Anna Fuji Rahimah; Budi Satrijo (Universitas Brawijaya, 2022)
BACKGROUND: Coronary artery disease (CAD) occurring in less than 45 years of age is termed as premature CAD (PCAD). Recent studies showed a prevalence of 4-10 % of PCAD. PCAD is associated with unfavorable outcomes for the patients and had a greater impact on the quality of life. Family History is the best method to explained complex interaction between shared risk factor.CASE ILLUSTRATION: A 37-years old male admitted to Saiful Anwar Hospital for further evaluation of anginal pain. The patient complains of recurrent chest pain since 5 months ago but still relieved by rest. The electrocardiogram showed Wellens Type B which is specific for critical stenosis of the left anterior descending artery (LAD). Then the patient undergoing DCA Ad Hoc. The implantation of a 46 mm DES at proximal until distal LAD was performed. The patient discharged after a day observation.DISCUSSION: The challenging point, in this case, was it happen at a young age with strong family history. There was positive family history of PCAD in 1st degree relative on her brother and mother, despite several risk factors were identified in this case consist of smoking, and dyslipidemia, which make CAD risk higher. Despite adequate control of risk factors, family screening is important to reveal subclinical atherosclerosis.CONCLUSION: Approach to a patient with PCAD comprises of management of traditional risk factors and careful investigation of Family History. Individual with positive family history of PCAD should be treated more cautiously